(untitled) (Research, Society and Development, 2025)
Postoperative infections in the immediate period following pediatric cardiac surgery represent a significant cause of morbidity and mortality, worsening clinical outcomes and increasing healthcare costs. Despite technical and therapeutic advances, the immunological vulnerability of neonates and the complexity of cardiac procedures favor the occurrence of early infectious complications. This study aims to conduct a narrative review of recent scientific literature on infections in the immediate postoperative period of pediatric cardiac surgeries. A narrative review was performed based on 18 articles published between 2020 and 2025, retrieved from scientific databases and selected according to predefined inclusion and exclusion criteria. The results showed that bloodstream infections, surgical site infections, ventilator-associated pneumonias, sepsis, and fungal infections were the most prevalent. Major risk factors included delayed sternal closure, prolonged mechanical ventilation, extended surgical time, need for ECMO, and the presence of invasive devices. Prevention strategies based on bundles, rational antibiotic prophylaxis, environmental control, and multiprofessional education proved effective in reducing cases. Treatment involved empirical antibiotic therapy guided by culture results and, in fungal cases, the use of specific antifungal agents. It is concluded that the adoption of standardized, evidence-based strategies is essential to reduce the incidence and severity of immediate postoperative infections in pediatric cardiac surgeries.